A Framework to Determine Prominent Research Topics and Experts from Google Scholar - Sarasjati, W.; Kumar, Y. J.; Goh, O. S.; Raza, B. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
In today’s digital era, most scholarly publications are made available online. These include the data of a university’s research publications which can be reached through Google Scholar. Determining the prominent research areas of a university and finding its experts is the motivation of this study. Although many people may be aware of the published articles of certain university researchers, however there are little or no information on the main research areas of the university where the researchers belong to. Thus, this study will investigate how the prominent research areas can be determined by implementing Refined Text Clustering (RTC) technique for clustering scholarly data based on the titles of publications. Then, an expert search approach can be used to determine the key players who are the experts in each research cluster. The Expert Finding System (EFS) is proposed by applying statistical analysis based on the total of number researcher’s publications and their number of citations.